2004
DOI: 10.1523/jneurosci.1346-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Double Dissociation between the Effects of Peri-Postrhinal Cortex and Hippocampal Lesions on Tests of Object Recognition and Spatial Memory: Heterogeneity of Function within the Temporal Lobe

Abstract: It is widely believed that declarative memory is mediated by a medial temporal lobe memory system consisting of several distinct structures, including the hippocampus and perirhinal cortex. The strong version of this view assumes a high degree of functional homogeneity and serial organization within the medial temporal lobe, such that double dissociations between individual structures should not be possible. In the present study, we tested for a functional double dissociation between the hippocampus and peri-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
447
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 536 publications
(508 citation statements)
references
References 51 publications
42
447
3
Order By: Relevance
“…Double dissociation studies confirmed these findings showing that animals with hippocampal lesions showed impairments in recognition memory but not in spatial memory and those with perirhinal lesions showed impairments in spatial memory but not in recognition memory (Ennaceur et al, 1996;Bussey et al, 2000;Winters et al, 2004). This dissociation between hippocampal and perirhinal function was conserved across rat strains (Futter et al, 2006) and species (Pihlajamä ki et al, 2004;Buckley, 2005;Kö hler et al, 2005).…”
Section: The Role Of the Perirhinal Cortex In Context And Spatial Memorysupporting
confidence: 59%
See 1 more Smart Citation
“…Double dissociation studies confirmed these findings showing that animals with hippocampal lesions showed impairments in recognition memory but not in spatial memory and those with perirhinal lesions showed impairments in spatial memory but not in recognition memory (Ennaceur et al, 1996;Bussey et al, 2000;Winters et al, 2004). This dissociation between hippocampal and perirhinal function was conserved across rat strains (Futter et al, 2006) and species (Pihlajamä ki et al, 2004;Buckley, 2005;Kö hler et al, 2005).…”
Section: The Role Of the Perirhinal Cortex In Context And Spatial Memorysupporting
confidence: 59%
“…Perirhinal lesion studies that do report spatial memory deficits also show some damage to the postrhinal cortex (Mumby and Glenn, 2000;Glenn et al, 2003) or also involve entorhinal cortex lesions (Nagahara et al, 1995). One combined perirhinal and postrhinal lesion study has reported impairments in spatial memory (Liu and Bilkey, 2001) but a number of other combined perirhinal and postrhinal lesion studies showed no deficits in spatial memory Bussey et al, 1999Bussey et al, , 2000Winters et al, 2004).…”
Section: The Role Of the Perirhinal Cortex In Context And Spatial Memorymentioning
confidence: 99%
“…In studies that examine recognition by monitoring spontaneous exploration of familiar and novel stimuli, monkeys with selective hippocampal or parahippocampal cortex damage that show little or no deficit in DNMS have severe and rapidly apparent deficits on the spontaneous novelty exploration task Nemanic et al, 2004). In rats, some studies report no deficit (e.g., Mumby, 2001;Mumby et al, 2002;Winters et al, 2004), whereas other studies have observed impairment at long delays Hammond et al, 2004), or following a large amount of damage to the hippocampus (Broadbent et al, 2004). In contrast to the modest and variable deficit observed following damage to the hippocampus, ablation of the perirhinal cortex consistently results in a severe and rapidly developing deficit in both kinds of recognition memory tasks in monkeys (Nemanic et al, 2004) and in rats (Mumby et al, 2002;Winters et al, 2004;Norman and Eacott, 2005;Winters and Bussey, 2005).…”
Section: Hippocampusmentioning
confidence: 99%
“…Furthermore, different test protocols are being used. For example, some studies use flexible sample trial durations, allowing all animals to reach a specific amount of object interaction [12,[30][31][32]. Other experiments have fixed sample trial durations and each individual animal differs in the amount of sample object exposure [1,11,25,33].…”
Section: Introductionmentioning
confidence: 99%